Effect of cooling strategies on milk production, physiological variables and blood profile during hot-dry and hot-humid summer in Sahiwal cattle - YADAV, B; MADAN, A K; YADAV, S; PANDEY, V; SIROHI, R (The Indian Journal of Animal Sciences, 2021)
The present experiment was undertaken to study the effect of misting and splashing during hot-dry and hothumid months in lactating Sahiwal cattle. The study was conducted during May, June (hot-dry) and July (hothumid) with monthly average temperature-humidity index (THI) of 79.88, 80.57 and 85.36, respectively. Eighteen lactating cattle were selected on the basis of days in milk, milk yield, and parity and then divided into three groups: control (no cooling), cooling by misting and cooling by splashing. Milk production was not affected by hot-dry and hot-humid heat stress in Sahiwal cattle. RT and RR were significantly lower in misting and splashing group as compared to control during hot-dry period. The heat stress-induced leucocytosis, lymphocytopenia and neutrophilia were significantly ameliorated by both misting and splashing during the study period. Heat stress-induced alterations in serum creatinine, sodium and ROS concentration were significantly mitigated by misting in hot-humid climate. The prolactin level significantly decreased in animals by misting during the study period. The results suggested that misting was more efficient than splashing as a cooling strategy in hot dry condition while splashing was more effective in hot-humid condition and mitigated the heat stress-induced alterations in different welfare parameters but could not fully nullify it. However, the resultant stress was not sufficient enough to decrease the milk yield in Sahiwal cattle. It may also be concluded that the Sahiwal cattle have high heat tolerance and could sustain production even in a hot-dry and hot-humid environment.